Family Harmony: Distribution of Inheritance to the Youngest Child in Gunung Meriah Aceh - Khairuddin, Khairuddin (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2024)
This paper aims to reveal the distribution of the inheritance of the youngest child in Gunung Meriah sub-district, Aceh Singki Regency. This study departs from a phenomenon where the youngest child gets more shares than other siblings, this is certainly different in the fiqh mawaris which explains if there are sons and daughters then sons get a share of 2: 1. This research belongs to the type of field research because the data is generated from informant answers. The data sources were obtained from religious leaders, community leaders, village heads, parents who distributed inheritance and children who received inheritance who had a broad understanding of the inheritance of the youngest child. Data collection was carried out by observation, interview and documentation methods. The results of this study showed that the youngest child in Gunung Meriah District received more shares of inheritance compared to other relatives, both the youngest child was a boy and a girl. The factor of giving more to the youngest child is because the youngest child is more economically less stable than his brother and brother, besides that the youngest child is the most tired and busy taking care of his parents, the youngest child after marriage usually stays at his parents' house. When viewed from Islamic law, the granting of inheritance to the youngest child is permissible because the distribution is based on deliberation and justice. [Tulisan ini bertujuan untuk mengungkap pembagian harta warisan anak bungsu di kecamatan Gunung Meriah Kabupaten Aceh Singki. Kajian ini berangkat dari sebuah fenomena dimana, anak bungsu mendapat bagian lebih banyak dibanding dengan saudara lainnya, hal ini tentu berbeda dalam fiqh mawaris yang menjelaskan jika ada anak laki dan anak perempuan maka anak laki-laki mendapat bagian 2:1. Penelitian ini termasuk dalam jenis penelitian lapangan karena datanya dihasilkan dari jawaban informan. Sumberdatatersebut didapat dari tokoh agama, tokoh masyarakat, kepala desa, orang tua yang membagikan harta warisan dan anak yang menerima warisan yang memilikipemahaman luas terkait pembagain hartawarisan anak bungsu. Pengumpulan data dilakukan dengan metode observasi, wawancara dan dokumentasi.hasil penelitian ini menunjukkan bahwa, anak bungsu di Kecamatan Gunung Meriah mendapat bagian harta warisan lebih banyak dibandingkan dengan saudara lainyya, baik anak bungsu tersebut berjenis kelamin laki-laki maupun perempuan. adapun faktor pemberian lebih kepada anak bungsu disebabkan karena anak bungsu lebih banyak ekonominya kurang mapan dibandingkan dengan abang dan kakaknya, selain itu juga anak bungsu paling capek dan sibuk mengurus orang tuanya, anak bungsu setelah menikah biasanya menetap dirumah orang tuanya. Jika dilihat dari hukum Islam, emberian harta warisan kepada anak bungsu merupakan hal yang diperbolehkan karena pembagaian tersebut berasaskan musyawarah dan berkeadilan].